Analysis of the Connections Between Law and Morals, Between Customs and Contemporaneity - Iovan, Marțian (Journal of Legal Studies, 2020)
This paper analyses the concepts of three great Romanian thinkers –theoreticians and philosophers of law – on the relations between law, morals and manners in order to discover, based on their idea filiation in the juridical Romanian culture, the differences of method and contents between them, to identify the practical implication in the field of performing the justice and law-making. Being trained and positioned in the core of the European juridical culture of their time, they reviewed the relations between law and morals, in a rationalist and humanist way, substantiating the need for the law to follow morals, the ethical principles both historically, and practically, the law-making being comprised as well. Thus, they leave room to the expression of human’s basic rights and freedoms in a democratic judicial order, while the rules of law subordinating the morals and manner proved to be widely open to totalitarianism.